2021
DOI: 10.12678/1089-313x.091521a
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Strength Training in Dance

Abstract: The aim of this study was to ascertain current perceptions of strength training (ST) in dance from the viewpoint of the professional dancer, dance teacher, and student dancers across dance genres. A total of 168 responses (149 females, 19 males) to the modified Training Information Survey (TIS) were analyzed for differences in perceptions of ST between dance students, professional dancers, and dance teachers. Some significant differences were found between professionals and teachers (p > 0.05) and between s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 26 publications
1
17
0
Order By: Relevance
“…These perceptions concur with recent research that demonstrates a sea-change in perceptions, particularly amongst students. 16,19 Prior research has stated that there is often misinformation on the importance of strength training to optimize performance in sport and dance, 23,24 particularly in relation to 19 In the current study, both dance and circus students neither agreed nor disagreed with the statement "Strength training is fun and enjoyable," 4.00 (IQR 0.00) and 4.00 (IQR 1.00) respectively and "Strength training enhances body and self-image," 4.00 (IQR 1.50) and 4.00 (IQR 1.00). It has been suggested that barriers to participation in strength training may be removed through an increase in education on the benefits and techniques of strength training 16,19 and that this may in turn lead to increases in intrinsically motivating factors.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These perceptions concur with recent research that demonstrates a sea-change in perceptions, particularly amongst students. 16,19 Prior research has stated that there is often misinformation on the importance of strength training to optimize performance in sport and dance, 23,24 particularly in relation to 19 In the current study, both dance and circus students neither agreed nor disagreed with the statement "Strength training is fun and enjoyable," 4.00 (IQR 0.00) and 4.00 (IQR 1.00) respectively and "Strength training enhances body and self-image," 4.00 (IQR 1.50) and 4.00 (IQR 1.00). It has been suggested that barriers to participation in strength training may be removed through an increase in education on the benefits and techniques of strength training 16,19 and that this may in turn lead to increases in intrinsically motivating factors.…”
Section: Discussionmentioning
confidence: 99%
“…Results demonstrate an understanding amongst dance students and professional dancers of the need for strength training and an agreement that it is beneficial to their performance as well as how they feel about themselves physically and mentally. 16 Previous literature relating to body composition in dance, described modern dancers as having a more muscular physique 21 and that they had a stronger focus on physiological demands rather than esthetic qualities. 16,22 No research has explored similar themes in circus students.…”
Section: Perceptions Of Strength Training In the Performing Artsmentioning
confidence: 99%
See 1 more Smart Citation
“…Progressive strength and conditioning programs that elicit increased power output are implemented in ballistic athletes to enhance stretch-shortening cycle (SSC) function (Cormie et al, 2010 ; Haff and Nimphius, 2012 ). As knowledge on the benefits of resistance exercise continually grows, additional training in ballistic athletes such as dancers, has become increasingly prevalent within dance companies, schools, and teams (Farmer and Brouner, 2021 ). Although the perception is shifting, optimal programming for dancers is still in the developmental stages (i.e., exercises, volume, intensity, and rest).…”
Section: Introductionmentioning
confidence: 99%
“…One of the reasons for this, has been the assumption that dancers are concerned (particularly in females) about increasing muscle mass and its impact on the aesthetic component of dance. However, a recent study with a mixed genre of professional dancers (19 ballet dancers included) has concluded that the dancers' perception is to not be afraid of muscle hypertrophy, which is a more prevalent preconception in dance teachers 10 . Due to the physical demands and physiological responses observed in professional ballet 11 , designing optimal training programs for dancers is a relevant area of research.…”
mentioning
confidence: 99%